The synergy of digital knowledge and skills in forming digital citizenship: a comprehensive assessment on nursing students - Purnama Sari, Ni Putu Wulan; Artsanthia, Jintana; Suvaree, Sudarat; Prachyakoon, Numpueng (Intelektual Pustaka Media Utama, 2025)
Nurses play a pivotal role in improving the quality of healthcare services through innovation in the nursing care delivery system by using technological advancement. Digital knowledge and mindset are useful for further developing digital skills and literacy among future nurses to form digital citizenship. This study aimed to analyze the correlation between digital knowledge and mindset with digital skills, literacy, and citizenship among nursing students. The mind sponge theory was used in study conceptualization and results interpretation. This quantitative study utilized a cross-sectional design. The population was all nursing students in two private nursing institutions located in Bangkok, Thailand (n=476) and Surabaya, Indonesia (n=179). Samples were the total population. Self-developed, valid, and reliable instrument was used in data collection. Descriptive statistics and correlation test were used in data analysis (α<.05). Findings showed that digital knowledge did not correlate with digital mindset (p=.94), but it was weakly correlated with digital skills, literacy, and citizenship (ρ=.12-.16; p<.05). Digital mindset was strongly correlated with digital skills, literacy, and citizenship (ρ=.56-.60; p<.05). Digital skills had a strong correlation with digital literacy and citizenship (ρ=.58-.67; p<.05), while digital literacy was strongly correlated with digital citizenship (ρ=.59; p=<.05). The synergy of digital mindset, skills, and literacy are recommended to support the digital citizenship formation. We strongly recommend the implementation of collaborative learning method in nursing education. This method promotes the information filtering and exchanging behaviors among students important for digital nursing.